2019
DOI: 10.1002/cssc.201802592
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Fate of Lignin from Eucalyptus and Poplar during Integrated Delignification and Bleaching

Abstract: Efficient deconstruction of lignocellulose is vitally important for the biorefinery industry because lignin structures play a crucial role in the high value‐added conversion of lignin. In this study, an integrated process based on hydrothermal pretreatment (HTP) and Kraft delignification was proposed to deconstruct lignocellulosic biomass. It was found that the HTP not only facilitated the production of xylo‐oligosaccharides but also reduced the chemicals dosage of the following delignification. The structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…91 In addition, lignin contains plentiful functional groups tending to form irreversible condensation at a higher temperature, especially for hydroxyl groups. 92,93 It is reported that the molecular weight and polydispersity of lignin increased after twin-screw extrusion because of the thermal condensation reaction inspired by hydroxyl groups, which was proven by GPC results where the average molecular weight of KL increased from 4420 to 10 230 g/mol. 94,95 Moreover, in our previous research, the β-O-4 linkage content of lignin decreased slightly after the hot-pressing process, but the condensed aromatic carbons (C−C bonds) increased, which indicated that the formation of new linkages would increase the molecular weight and cross-linking structures.…”
Section: ■ Blending Process Of Lignin Into Biodegradable Polyester-ba...mentioning
confidence: 94%
“…91 In addition, lignin contains plentiful functional groups tending to form irreversible condensation at a higher temperature, especially for hydroxyl groups. 92,93 It is reported that the molecular weight and polydispersity of lignin increased after twin-screw extrusion because of the thermal condensation reaction inspired by hydroxyl groups, which was proven by GPC results where the average molecular weight of KL increased from 4420 to 10 230 g/mol. 94,95 Moreover, in our previous research, the β-O-4 linkage content of lignin decreased slightly after the hot-pressing process, but the condensed aromatic carbons (C−C bonds) increased, which indicated that the formation of new linkages would increase the molecular weight and cross-linking structures.…”
Section: ■ Blending Process Of Lignin Into Biodegradable Polyester-ba...mentioning
confidence: 94%
“…Topically, tobacco stalks were cut into 3–5 cm length, then milled into 40–60 mesh powder, and oven-dried at 60°C for 48 h. Chemical compositions of the stalk are cellulose (40.5 wt%), hemicelluloses (21.5 wt%), lignin (22.3 wt%), and others (15.7 wt%), which are determined according to the National Renewable Energy Laboratory (NREL) method ( Sluiter et al, 2008 ). Hydrothermal pretreatment (HTP) of tobacco stalk was performed in a stainless-steel reactor (Parr, United States) with a solid-to-liquid ratio of 1:8 (g/ml) at 170°C for 1 h ( Wang et al, 2019b ). Afterward, the treated tobacco stalks were separated by nylon gauze and oven-dried (60°C) to obtain HTP tobacco stalk.…”
Section: Methodsmentioning
confidence: 99%
“…CEL is also considered as a desirable sample to characterize the structure of lignin, which was similar to that of MWL. The extraction of CEL was mainly divided into three stages: (i) the lignocellulose was ball milled for about 5 h; (ii) the ball milled lignocellulose is then hydrolyzed by composite enzymes of cellulose and hemicelluloses to digest carbohydrates into monosaccharides; and (iii) the solids obtained after the enzyme hydrolysis are then treated by 96% of dioxane to extract CEL, and the detailed processes are same as the extraction of MWL [21,22]. Although the structural features of CEL were similar to those of MWL, the yield of CEL was apparently enhanced.…”
Section: Cellulolytic Enzyme Lignin (Cel)mentioning
confidence: 99%